2013
DOI: 10.1155/2013/481830
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Glycyrrhetinic Acid on the Delayed Rectifier Potassium Current in Guinea Pig Ventricular Myocytes and HERG Channel

Abstract: Background. Licorice has long been used to treat many ailments including cardiovascular disorders in China. Recent studies have shown that the cardiac actions of licorice can be attributed to its active component, glycyrrhetinic acid (GA). However, the mechanism of action remains poorly understood. Aim. The effects of GA on the delayed rectifier potassium current (I K), the rapidly activating (I Kr) and slowly activating (I Ks) components of I K, and the HERG K+ channel expressed in HEK-293 cells were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These properties are partly due to GA’s mineralocorticoid and glucocorticoid receptor binding capacity as well as to 11β-hydroxysteroid dehydrogenase inhibition (Armanini et al, 1983). Furthermore, GA blocks Ca 2+ currents in rat mesenteric small arteries (10 µM) (Matchkov et al, 2004), Cl - conductance in primary rat hepatocytes (40 µM) (Böhmer et al, 2001), delayed rectified K + currents in guinea pig ventricular myocytes (1, 5 and 10 µM) (Wu et al, 2013), Cx50 and Cx46 HCs (2 µM) (Bruzzone et al, 2005; Eskandari et al, 2002) as well as Panx1 channels and P 2 X 7 receptors (half maximal inhibitory concentration (IC 50 ) 50 µM) in X. laevis oocytes (Bruzzone et al, 2005; Locovei et al, 2007) (Table 2). GA affects many different GJs without being Cx subtype specific (Bodendiek & Raman, 2010), but detailed selectivity studies are lacking.…”
Section: Chemical-based Inhibitorsmentioning
confidence: 99%
“…These properties are partly due to GA’s mineralocorticoid and glucocorticoid receptor binding capacity as well as to 11β-hydroxysteroid dehydrogenase inhibition (Armanini et al, 1983). Furthermore, GA blocks Ca 2+ currents in rat mesenteric small arteries (10 µM) (Matchkov et al, 2004), Cl - conductance in primary rat hepatocytes (40 µM) (Böhmer et al, 2001), delayed rectified K + currents in guinea pig ventricular myocytes (1, 5 and 10 µM) (Wu et al, 2013), Cx50 and Cx46 HCs (2 µM) (Bruzzone et al, 2005; Eskandari et al, 2002) as well as Panx1 channels and P 2 X 7 receptors (half maximal inhibitory concentration (IC 50 ) 50 µM) in X. laevis oocytes (Bruzzone et al, 2005; Locovei et al, 2007) (Table 2). GA affects many different GJs without being Cx subtype specific (Bodendiek & Raman, 2010), but detailed selectivity studies are lacking.…”
Section: Chemical-based Inhibitorsmentioning
confidence: 99%
“…In the same way, glycyrrhetinic acid, a component of licorice root ( Glycyrrhiza glabra ) dose-dependently blocked IKr and IKs in guinea pig ventricular myocytes. 21 , 22 The peculiarity of the effects of H. bonariensis leaf extract that emerges from our work is its selective inhibition of the IKs current. In human myocardium, in the absence of β-adrenergic stimulation, inhibition of IKs induces little or no effect on the duration of action potential repolarization and on the QT interval.…”
Section: Discussionmentioning
confidence: 84%
“…The inhibition of these currents predisposes the prolongation of AP and ERP that cause arrhythmias prevention. 80 Another survey on human atrial myocytes and Xenopus oocytes indicated that 18β-glycyrrhetinic Acid inhibits both the peak Na + current and the late Na + current in a dose-dependent pattern. These effects suggest that 18β-glycyrrhetinic acid can have antiarrhythmic potential.…”
Section: Plants and Their Ingredients With Antiarhythmic Propertiesmentioning
confidence: 99%